Recontextualizing Clarence Ayres's The Theory of Economic Progress through Archival Evidence. Issue 2 (2nd April 2020) - Almeida, Felipe; Goulart, Gustavo
Abstract: Our article seeks to recontextualize Clarence Ayres's The Theory of Economic Progress through a reconsideration of the criticisms of the book and Ayres's personal standpoint on it. We believe that the negative reception of the book conveys the mainstream perspective. Additionally, our article stresses some of Ayres's thoughts on Western society that were not included in The Theory of Economic Progress but were introduced by him through correspondence around the same time his famous book was written and disseminated. We conclude that Ayres was more radical than his writings reveal.